1996
DOI: 10.3109/00365529609036903
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric pH during Treatment with Omeprazole: Role ofHelicobacter pyloriandH. pylori-Associated Gastritis

Abstract: The increased pH produced by omeprazole during H. pylori infection is likely to be due to neutralizing substances produced by H. pylori and not to H. pylori-induced gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 10 publications
2
38
0
1
Order By: Relevance
“…pylori eradication therapy also has the potential to impact significantly on reflux disease, through the effects of H. pylori eradication on acid secretory capacity and the pH of the gastric content [36,37]. When H. pylori infection is cured, a significant component of non-atrophic gastritis resolves, and acid secretory capacity can recover substantially [37].…”
Section: H Pylori Infection and Reflux Diseasementioning
confidence: 99%
“…pylori eradication therapy also has the potential to impact significantly on reflux disease, through the effects of H. pylori eradication on acid secretory capacity and the pH of the gastric content [36,37]. When H. pylori infection is cured, a significant component of non-atrophic gastritis resolves, and acid secretory capacity can recover substantially [37].…”
Section: H Pylori Infection and Reflux Diseasementioning
confidence: 99%
“…It has been shown that the intragastric pH is significantly higher with the same dose of PPI before as compared to after H. pylori eradication [31,32]. …”
Section: Helicobacter Pylori Infection and Interaction With Acid-inhimentioning
confidence: 99%
“…All of these pathophysiological factors might be indicative of an increased gastro-oesophageal reflux [6]. Two arguments that would militate against such a relationship would be the buffering effect of the ammonia produced by the bacteria, resulting in a reduction in the amount of acid in the stomach [7, 8], and elevated gastrin levels [9]leading to an increase in lower oesophageal sphincter pressure [10]. The question arises whether the Hp-induced gastritis can protect against the development of gastro-oesophageal reflux disease (GORD) [11, 12].…”
Section: Introductionmentioning
confidence: 99%